Life history mediates the trade‐offs among different components of demographic resilience. (25th March 2022) - Capdevila, Pol; Stott, Iain; Cant, James; Beger, Maria; Rowlands, Gwilym; Grace, Molly; Salguero‐Gómez, Roberto
Abstract: Accelerating rates of biodiversity loss underscore the need to understand how species achieve resilience—the ability to resist and recover from a/biotic disturbances. Yet, the factors determining the resilience of species remain poorly understood, due to disagreements on its definition and the lack of large‐scale analyses. Here, we investigate how the life history of 910 natural populations of animals and plants predicts their intrinsic ability to be resilient. We show that demographic resilience can be achieved through different combinations of compensation, resistance and recovery after a disturbance. We demonstrate that these resilience components are highly correlated with life history traits related to the species' pace of life and reproductive strategy. Species with longer generation times require longer recovery times post‐disturbance, whilst those with greater reproductive capacity have greater resistance and compensation. Our findings highlight the key role of life history traits to understand species resilience, improving our ability to predict how natural populations cope with disturbance regimes. Abstract : Understanding how the resilience of species arises has become a key question in ecology and conservation. Here, we find that the demographic resilience of species is determined by three interrelated components: resistance, compensation and time of recovery. Moreover, these components of resilience are highly determined by key life history traits, such as generation time and mean reproductive output.